Creating Personal Expressions In Expanded Drawing Artworks Through A Synectic Approach - mubaroh, mufi; Arifin, Mohamad (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
Expanded drawing is an investigation of the evolution of drawing techniques and media/materials that have given artists the freedom to experiment, venture outside of their comfort zones, and change their routines. Extended drawing offers difficult activity engagements by fusing media and techniques with imaginative concepts. It also expands and reframes traditional drawing disciplines and approaches to produce works with a vibrant, modern personality. To create works that allude to distinctive traits and processes, media and technique development is done while keeping a larger context in mind. New media or media that has been used frequently are both used in this process. With its ability to create a dynamic and imaginative arena, Drawing Expanded is full of exploration, responding to medium and drawing styles in accordance with the concept being created. Expanded drawing is a new definition that arises from redefining, based on the individual's choice of media and technique as well as the environment. American artist Robert Morris first used the word in 1946 to describe a three-dimensional approach outside galleries that highlighted the value of creative exploration and interaction with materials, media, techniques, locations, and ideas.